Analysis of the Oil and Petrochemical Integrated Refinery Development Plan's environmental impact and its mitigation of public health status - Endang Susilowati; Sukriyah Kustanti Moerad; Deti Rahmawati; Niken Prasetyawati (Institut Teknologi Sepuluh Nopember, 2022)
Development is a social process that aims to enhance the environment and the quality of communal life. Sustainability happens as a result of the environment serving as a living space and a source of additional value. The following environmental factors must be integrated into a development plan: biogeophysics, social, economic, cultural, and public health. PT PERTAMINA (Corporate Company) in collaboration with Rosneft Oil Company will build and operate a new oil and petrochemical integrated refinery and its supporting facilities. About 27,000 people were hired for the building phase, and about 3,000 for the operation phase. This study aims to lessen the detrimental effects of development plans on public health. This qualitative study is a cross-sectional descriptive investigation of the area surrounding the proposed refinery in East Java Province, Indonesia's Jenu District and Tuban Regency. The study's findings were determined through firsthand observation and a poll of 100 residents who would be impacted by the development plan. The findings show that, in order to prevent environmental disputes, environmental management and monitoring must be carried out.